2017
DOI: 10.5935/1414-8145.20170028
|View full text |Cite
|
Sign up to set email alerts
|

Reference and counter-reference health care system of infant discharged from neonatal unit: perceptions of primary care health professionals

Abstract: Objective: To identify how the references and counter-references occur in the care of preterm, low and/or very low birth weight newborn after discharge from the Neonatal Unit in the Health Care System. Methods: Qualitative, exploratory-descriptive research.A total of 31 professionals from the Primary Health Care Units, Joinville/SC, were interviewed from September to October, 2014.Categorical thematic content analysis was used. Results: Three categories emerged. Communication between the reference hospital and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
26

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 11 publications
0
19
0
26
Order By: Relevance
“…[17][18] Despite the different conceptions, it is important to point out that studies have indicated fragilities in the aspects that involve comprehensive care, whether in the availability of health care services and sectors when the child presents needs, or through the care that remains based on the biological model, not understanding that children are influenced by their family and the context they live in. [19][20][21][22] This care is often fragmented, without interlocution between sectors and services, 23 and with little interaction and communication between professionals and family. [24][25] Nevertheless, a path can be outlined that considers comprehensiveness, an essential aspect for care, which takes place as the children are understood in their entirety, in the family and community context, taking into account the issues that form and shape them as individuals, with respect for their singularities.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18] Despite the different conceptions, it is important to point out that studies have indicated fragilities in the aspects that involve comprehensive care, whether in the availability of health care services and sectors when the child presents needs, or through the care that remains based on the biological model, not understanding that children are influenced by their family and the context they live in. [19][20][21][22] This care is often fragmented, without interlocution between sectors and services, 23 and with little interaction and communication between professionals and family. [24][25] Nevertheless, a path can be outlined that considers comprehensiveness, an essential aspect for care, which takes place as the children are understood in their entirety, in the family and community context, taking into account the issues that form and shape them as individuals, with respect for their singularities.…”
Section: Introductionmentioning
confidence: 99%
“…The participation of primary care professionals in KMCM is still shy and preterm and/or low-weight NB care permeated with insecurity (31,41) . The results show the need to strengthen the role of the family in early hospitalization (third stage), review discharge criteria, ensure all possibilities of continued care (32)(33)42) .…”
Section: -Familymentioning
confidence: 99%
“…Diferentes estudos evidenciaram a falha no diálogo entre as equipes, devido à ausência de conhecimento sobre o fluxo de comunicação institucionalizado, falta de planejamento, consolidação e definição desses serviços aos profissionais que atuam nessa área, inexistência da contrarreferência em grande parte dos casos, fragmentação dos serviços de saúde e desarticulação dos diferentes setores do SUS, contrapondo a proposta de um sistema unificado 1,7,12,[14][15][16] .…”
Section: Discussionunclassified
“…A comunicação entre os profissionais das unidades de todos os níveis de atenção ainda ocorre de modo deficiente. Por isso, é muito importante o estabelecimento de um vínculo entre eles, para que ocorra o fortalecimento da comunicação interinstitucional, a fim de garantir um atendimento de qualidade e com continuidade 7 .…”
Section: Introductionunclassified